Super‐Elastic Carbonized Mushroom Aerogel for Management of Uncontrolled Hemorrhage - Yang, Ganghua; Huang, Zhenzhen; McCarthy, Alec; Huang, Yueyue; Pan, Jingye; Chen, Shixuan; Wan, Wenbing (Advanced science, 2023)
Uncontrolled hemorrhage is still the most common cause of potentially preventable death after trauma in prehospital settings. However, there rarely are hemostatic materials that can achieve safely and efficiently rapid hemostasis simultaneously. Here, new carbonized cellulose‐based aerogel hemostatic material is developed for the management of noncompressible torso hemorrhage, the most intractable issue of uncontrolled hemorrhage. The carbonized cellulose aerogel is derived from the Agaricus bisporus after a series of processing, including cutting, carbonization, purification, and freeze‐drying. In vitro, the carbonized cellulose aerogels with porous structure show improved hydrophilicity, good blood absorption, and coagulation ability, rapid shape recoverable ability under wet conditions. And in vivo, the carbonized aerogels show effective hemostatic ability in both small and big animal serious hemorrhage models. The amount of blood loss and the hemostatic time of carbonized aerogels are all better than the positive control group. Moreover, the mechanism studies reveal that the good hemostatic ability of the carbonized cellulose aerogel is associated with high hemoglobin binding efficiency, red blood cell absorption, and platelets absorption and activation. Together, the carbonized aerogel developed in this study could be promising for the management of uncontrolled hemorrhage. In this study, carbonized cellulose aerogels derived from Agaricus bisporus are developed for intraperitoneal hemostasis. The carbonized cellulose aerogels with porous structure show improved hydrophilicity, good blood absorption, and coagulation ability, and rapid shape recoverable ability under wet conditions. Furthermore, the carbonized aerogels show effective hemostatic ability in both in vitro and in vivo studies.